The Impact of AI on Secure Cloud Computing: Opportunities and Challenges - Jones, Rebet (The Indonesian Journal of Computer Science, 2024)
This paper explores the intersection of Artificial Intelligence (AI) and cloud computing, focusing on the security implications. As cloud computing becomes increasingly ubiquitous, the integration of AI presents both opportunities and challenges. This paper provides an in-depth analysis of how AI can enhance cloud security, the potential risks associated with AI deployment in the cloud, and the future landscape of AI-driven cloud security. Key topics include AI's role in threat detection, data protection, access management, and the challenges related to AI bias, interpretability, and adversarial attacks.